A measurement scale for students’ usage of online networks - Barker, Rachel; Ong, Derek Lai Teik * (University of the Free State, 2016)
Studies suggest that students are increasingly turning to information and communication technologies as learning tools in which they can present multiple identities quite explicitly tied to context, knowledge and understanding within online networks. Hence it is imperative for educational institutions to understand how twenty-first-century learners use online networks for their identity formation and learning experiences. Through a systematic review of existing instruments, constructs and elements were identified and used to develop a new conceptual research framework which was quantitatively tested on a convenience sample of students (n=300) at Sunway University in Malaysia. Based on the results, a measurement scale was developed and analysed through structural equation modelling and confirmatory factor analysis. The responses of the students revealed they are more likely to use online networks for identity formation than for the learning experience and that there is a relationship between identity formation, the learning experience and the use of online networks.